STUDI KUALITAS LINGKUNGAN PERAIRAN PESISIR TELUK TERIMA, BALI - Made Dwi Wahyuni (Bumi Lestari Journal of Environment)
The study examined the environmental quality of Teluk Terima coastal area. The aimsof the study were to measure the degree of water pollution at Teluk Terima coastal arearesulted from tourism, human and agricultural activities, and to analyze physical andchemical properties of water, which affected diversity index of makrozoobenthos.The research applied analytical descriptive method. Samples were determined usingpurposive sampling, collected from 9 stations and replicated three times. Water quality wasdetermined by scoring and t test to calculate differences in pollution level among stations,and multiple regression test was used to calculate effects of physical and chemical propertiesof water on diversity index of makrozoobenthos.The results of the experiment showed that three parameters of water quality exceededthe threshold level, namely: suspended solids, clearness, and nitrite. The dominant substratewas consisted of sand (80.58% - 96.28%) with low value of clay (1.24% - 9.06%). About 27species of benthos (Gastropoda, Pelecypoda and Polychaeta) were examined. Substrate thatcontained more clay was dominated by Nereis sp, Nephtys sp and Polyphysia sp. withabundance of 101 ind/192,5 cm2, while at the more sandy area was dominated by Nerita sp.at abundance of 24 ind/192,5 cm2. The diversity index of makrozoobenthos was between1.059 – 1.885. The result on the integrated water quality analyses showed that the waterquality of Teluk Terima coastal area was classified between slight to moderate pollution.Multivariate regression analyses showed that the physical and chemical properties of waterdid not have a significant correlation and its effect was not significant on the diversity indexof makrozoobenthos.